Why less? The Gendered Aspects of Small- and Medium-sized Enterprise (SME) Ownership under Economic Transition - Ruta Aidis (Tinbergen Institute, 2002)
This paper explores the gendered influence on SME development under economic transition in Lithuania. Previous studies have shown that male and female business owners are more different than similar in terms of personal and business characteristics (Brush 1992). An analysis of 332 SME owners in Lithuania using descriptive statistics and regression analysis indicates that there are significant differences not only in objective criteria such as business size and business turnover but also in terms of subjective criteria such as perceived business financial 'success' and general business 'success'. Gendered expectations such as norms, values and social expectations (i.e. informal rules) that have been internalized or continue to exert external pressure seem to be at the heart of this discrepancy.
Keywords: 330; SMEs; gender; transition economies; Lithuania; entrepreneurship.; KMU; Entrepreneurship-Ansatz; Geschlecht; Übergangswirtschaft; Litauen